LEGAL FRAMEWORK FOR FAMILY POLICY BASHKIR ASSR IN 1917-1937-th - Gashura G. Gnıуаtullınа (Вестник Северо-Кавказского федерального университета, 2022)
The article examines the peculiarities of the legal framework of the Soviet family policy in 1917-1937 gg. in the Bashkir ASSR. Analyzes the content and application of legal acts of the state. The author has attempted to show how the legislative activity of the state in the field of marriage and family for twenty years.